T-box transcription factor eomesodermin/Tbr2 in Atlantic cod (Gadus morhua L.): Molecular characterization, promoter structure and function analysis - Chi, Heng; Sørmo, Kristian Gillebo; Diao, Jing; Dalmo, Roy Ambli (Fish & Shellfish Immunology, 2019)
Eomesodermin (Eomes) is a member of T-box transcription factor family and plays an important role in the regulation of a wide variety of developmental processes and immune response in animals. Here we report cloning and characterization of the full-length cDNA of Atlantic cod Eomes (GmEomes), which possesses a TBOX_3 domain similar to its counterpart in mammals. The regulated expression was observed in head kidney and spleen in response to live Vibrio anguillarum infection in vivo , and spleen leukocytes in vitro after PMA and poly I:C stimulation. Furthermore, we determined a 694 bp sequence, upstream of the transcriptional start site (TSS), to contain a number of sequence motifs that matched known transcription factor-binding sites. Activities of the presumptive regulatory gene were assessed by transfecting different 5′-deletion constructs in CHSE-214 cells. The results showed that the basal promoters and positive transcriptional regulator activities of GmEomes were dependent by sequences located from −694 to −376 bp upstream of TSS. Furthermore, we found that some Eomes binding sites were present in the 5′-flanking regions of the cod IFNγ gene predicted by bioinformatics. However, Co-transfection of eomesodermin overexpression plasmids with INFγ reporter vector into CHSE-214 cells determined that Atlantic cod eomesodermin played a minor role in activation of the INFγ promoter.